Window and door handle color selection (RFA-467_Rev B) - WOHA Designs PTE LTD; BUCG-ABC Joint Venture; Web Structures (2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of only PDF version of drawings.